The effect of return on asset, return on equity and economic value added towards market value added: evidence of Kuala Lumpur Stock Exchange / Anaz Zulaika Basman - Basman, Anaz Zulaika (2017)
This research conducted to examine the effect of return on asset (ROA), return on equity (ROE) and economic value added (EVA) towards market value added (MVA) in Kuala Lumpur Stock Exchange (KLSE). At the same time, this study also want to investigate the relationship between return on asset (ROA), return on equity (ROE) and economic value added (EVA) towards market value added (MVA). The sample involves 25 companies listed in Kuala Lumpur Stock Exchange (KLSE) over the period 2007 until 2016. Then, there are not significant effect in this study for independent variables towards the dependent variable. Meanwhile, there are positive correlation between return on asset (ROA), return on equity (ROE) and economic value added (EVA) towards market value added (MVA). These findings are in parallel with empirical evidence and theoretical perspective that been used. The study has implications for the managers who are responsible to generate the wealth of the shareholders formulating the corporate financial policies and for the investors who are concerned about the firm‟s financial health while taking the investment decision.